Characterization in ancient Greek literature - Temmerman, Koen de.; Emde Boas, Evert van, 1982- (Mnemosyne, Supplements, 2017)
Characterization in Ancient Greek Literature is the fourth volume in the series Studies in Ancient Greek Narrative. The book deals with the narratological concepts of character and characterization and explores the textual devices used for purposes of characterization by ancient Greek authors spanning a large historical period (from Homer to Heliodorus) and a variety of literary genres (epic, elegy, historiography, choral lyric, drama, oratory, philosophy, biography, and novel). The book's aim is not only to describe these devices, but also to investigate their effects and the implications of their use for our interpretation of the texts.